Total plate count and Salmonella spp. in de-boned milkfish (Chanos chanos) in Palu City, Indonesia - Ndobe, Samliok; Merpati, Ellen Oktanike; Rusaini, Rusaini; Serdiati, Novalina; Rusdi, Rusdi (Depik, 2023)
High total plate count (TPC) and the presence of Salmonella spp. in food products can cause health problems for consumers. De-boned milkfish products are popular with consumers in Palu City, Central Sulawesi, Indonesia, but there is a lack of data on their safety. Therefore, this study aimed to investigate TPC levels and detect contamination by Salmonella spp. in these products. Samples of fresh and processed milkfish were collected from two de-boned milkfish processing sites: the Technical Implementation Unit for the Application of Fishery Product Quality Control (TIU-AQFP) and the Melona Micro, Small and Medium Enterprise (MSME) Group in Palu City. Microbiological assays included counting the number of bacterial colonies (TPC) as well as the isolation and identification of Salmonella spp. through biochemical tests. The study applied a completely randomized factorial design with three replicates per site and per product (12 experimental units). De-boning had a significant (P0.05) effect on TPC (1.26103 to 2.20103 CFU/g for de-boned milkfish compared to 4.28103 to 2.94104 CFU/g for fresh unprocessed milkfish). However, the types of bacteria identified in fresh and de-boned milkfish, including Klebsiella, Enterobacter and Citrobacter, were present at non-pathogenic levels. No Salmonella spp. contamination was found in the test samples. These results indicate that de-boned milkfish products from the TIU-AQFP and Melona MSME Group in Palu City are safe and suitable for human consumption.Keywords:Bone-free milkfishBacterial contaminationPathogen assayFish processingFood safety